From the “Man of Jerusalem” to the Beit El Yeshiva: Late Nineteenth Century Rabbinic Leadership in the Jewish Community of Tripoli - Atia, Ronel (The review of rabbinic Judaism, 2021)
Abstract This article details a polemic among the rabbinical leadership of the Jewish community of Tripoli, Libya, in the late nineteenth century. At stake was an initiative of the community’s spiritual leader, Rabbi Eliyahu Bechor Hazzan, to change the traditional educational system to include secular topics and foreign language. The communal rabbis who opposed the idea wrote the rabbinical leadership of Jerusalem, requesting support in overturning Rabbi Hazzan’s proposal. This study details the issues at stake in this aspect of the infiltration of modernism into Jewish communities in Muslim countries and presents the letter written to the rabbinic authorities of the land of Israel that led Rabbi Hazzan to abandon his initiative and, later, to resign from his leadership post.